2022
DOI: 10.1177/08927057221128188
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties of calcium phosphate reinforced polyhydroxyalkanoate (PHA) biocomposite

Abstract: In the area of bone tissue engineering, the concept of using biomaterials based bone scaffolds in the regeneration of critical size bone defects is a key element to development of alternatives to allogenic and autogolous bone graft. Globally, countries all over the world is experiencing population aging besides other bone defects related case including trauma, pathology and congenital defects. Calcium phosphate (CaP) has received much interest for broad range of bone substitutes since its physicochemical prope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 47 publications
(50 reference statements)
0
6
0
Order By: Relevance
“…Bonarstev et al detailed the various types of PHA and their usages in commercially available medical products [87]. Najah et al created a biocomposite containing calcium phosphate, PHA, and chitosan to enhance the strength of the composite for bone graft applications [134]. The study showed that maximum tensile stress and elastic modulus could be achieved at 15 wt% of calcium phosphate [134].…”
Section: Diverse Types Of Food Waste-derived Materials As Essential C...mentioning
confidence: 99%
“…Bonarstev et al detailed the various types of PHA and their usages in commercially available medical products [87]. Najah et al created a biocomposite containing calcium phosphate, PHA, and chitosan to enhance the strength of the composite for bone graft applications [134]. The study showed that maximum tensile stress and elastic modulus could be achieved at 15 wt% of calcium phosphate [134].…”
Section: Diverse Types Of Food Waste-derived Materials As Essential C...mentioning
confidence: 99%
“…To overcome these limitations, several ongoing studies are exploring innovative techniques and improved materials to enhance the capabilities of bioceramics. 24,[79][80][81] These endeavors seek to overcome the challenges associated with their mechanical properties, promote enhanced strength and resilience, and ensure compatibility with the natural regeneration processes of bone. 82…”
Section: Bioceramics For Bone Regenerationmentioning
confidence: 99%
“…The composite exhibited a drop in these properties at a level approximately three times lower than that of neat PHA. 79 In another study by Monia (2022), a bone implant (β-TCP/DCPD-PHBV) based on Poly(hydroxybutyrate-co-hydroxyvalerate) (PHBV) and bioceramic β-TCP/DCPD demonstrated efficacy in healing bone defects. Mechanical investigations revealed that this biomaterial possessed satisfactory mechanical strength (195.21 MPa), which closely resembled that of natural bone.…”
Section: Recent Biocomposite Polymer-ceramic Applied In Bones Regener...mentioning
confidence: 99%
See 1 more Smart Citation
“…Their compositions are widely similar to those of the mineral phase of the bone. 14 Regarding its fragility, this material must not be used in bones under high loads. 15…”
Section: Introductionmentioning
confidence: 99%